Incorporación de normas en el código orgánico de la niñez y la adolescencia destinadas a sancionar el incumplimiento de los deberes de los medios de comunicación respecto a la formación educativa y cultural de los niños y adolescentes. - Ortíz Napa, Francisca Amparo (2011)
The Constitution of the Republic of Ecuador, recognizes children and teenagers, as one of the priority groups of Ecuadorian society, they deserve preferential protection in both the public and private, because of this, determined that the Ecuadorian state must take some policies for the realization of their rights, including talk of a special protection against the negative influence caused by the media, for which public policy in this area rather promote the education of children and adolescents, and respect for their rights. Consistent with the constitutional provision in the Code of Children and Adolescents, is established as a guarantee of the right to information, through the media should disseminate information of social interest for children and adolescents, and refrain from submitting material or software that can affect their overall development. The constitutional and legal provisions to which I referred in the above lines are explicitly broken by the Ecuadorian media, where daily and all time girls and adolescents can access the most extensive and normal , information that can be dangerous for their integral development and the proper formation of their personality. It is therefore necessary to conduct an investigation to examine the existing legal framework on the right to information of children and adolescents, determine the weaknesses can be identified in it, and raise legal remedies against this problem that is present in Ecuadorian society and threatens the development of these individuals given their chronological development, are likely to be victims of negative impact generated through the media. This paper confronts the issue in question, through the development of a comprehensive theoretical framework, conceptual, legal and doctrinal, and results obtained through the application of field techniques, this analysis allows us to gather the evidence enough to the end of the study the approach of a proposed amendment to the Code of Children and Adolescents, which is intended to ensure that the right to information is a means through which children and adolescents, to properly train his personality, and achieve their full development, thus achieving that the media play their leading role for society.